Induction of fuzzy rules from chemical process data using Growing Neural Gas and Reactive Tabu search methods - Gouws, Francois Stefan (Stellenbosch : Stellenbosch University, 2012)
Dissertation PhD(Ing) -- University of Stellenbosch, 1999.